Mental Health Education in the Quran - Farhan Mubarok Lubis (Pusdikra Publishing, 2026)
Mental health has become an increasingly important issue in contemporary society due to rapid social, technological, and cultural changes that contribute to psychological challenges such as anxiety, stress, and depression. This study aims to explore the concept and principles of mental health education as presented in the Holy Quran and to examine its relevance to individual, family, and societal well-being. The research employs an inductive thematic approach by collecting and analyzing Quranic verses related to mental health, supported by classical Quranic exegesis and relevant scholarly literature. The findings reveal that the Quran presents a comprehensive framework for mental health by integrating spiritual, psychological, and moral dimensions. Mental health in the Quran is closely associated with inner peace, emotional balance, and spiritual well-being, all of which are achieved through faith in Allah, sincere worship, remembrance of Allah (dhikr), patience, prayer, trust in divine decree (tawakkul), and contentment with His will (riḍā). These principles serve not only as preventive measures against psychological distress but also as therapeutic guidance for overcoming emotional and mental difficulties. The study concludes that the Quran offers a holistic educational model for nurturing mental health that harmonizes spiritual values with psychological resilience. Consequently, integrating Quranic teachings into mental health education can contribute significantly to promoting psychological stability, strengthening moral character, and enhancing the overall quality of life in contemporary Muslim communities.